PERANCANGAN APLIKASI PENGGAJIAN KARYAWAN BERBASIS WEB MENGGUNAKAN FRAMEWORK CODEIGNITER PADA PO ARISTA TEHNIK JAKARTA - Reza Fahlevi; Zulhalim Zulhalim; Asih Septia Rini (Sekolah Tinggi Manajemen Informatika dan Komputer Jayakarta, 2021)
Arista Tehnik Jakarta is an individual company engaged in manufacturing services for AC ducting in buildings. Arista Tehnik Jakarta in processing employee payroll data still uses the manual / conventional method, which is taking notes on bookkeeping so that errors often occur in calculating employee salaries. Calculating employee salaries can have fatal consequences if something goes wrong and it can affect the preparation of payroll reports. The manual / conventional payroll system is not able to provide adequate benefits for calculating employee salaries. With a good payroll system, every company that already has many employees is very much needed. Companies that have many employees definitely need a payroll system that can make it easier to pay salaries appropriately and efficiently. The method used in this research is by making observations, interviews, literature studies, designing information systems followed by the development of information systems and then testing. The result of this research is to produce a computerized payroll information system that provides convenience in providing payroll data information such as employee data information, job data and payroll data. In the Payroll Data Information System using UML (Unified Modeling Language), programming using the CodeIgniter framework, and MySQL for database processing. After the researcher then created a Payroll Information System, the work procedure could be easier for Arista Tehnik Jakarta.